Fostering Learner Autonomy in EFL Classroom: The Impact of New Learning Guidelines and Relational Pedagogy - EPPENDI, Jhoni; ANWAR, Azwar; LAKSANA, Jamie Anugerah Keeyan (Politeknik Negeri Ujung Pandang, 2025)
Learner autonomy is a critical outcome in EFL education, yet the mechanisms through which instructional frameworks and educator behavior influence autonomous learning remain underexplored. This study investigates the impact of the New Learning Guidelines, a structured pedagogical framework, on the development of learner autonomy among undergraduate EFL students. Employing an explanatory sequential mixed-methods design, the study involved 539 students categorized into positive (n = 78) and negative (n = 462) attitudinal groups. The quantitative data were collected through structured questionnaires, and qualitative data were collected via semi-structured interviews. Quantitative findings revealed that students with positive attitudes demonstrated substantial gains in goal setting, strategic planning, and self-monitoring, whereas those with negative attitudes showed limited improvement from structure alone. Thematic analysis underscored the role of relational scaffolding, emotionally responsive, supportive teacher-student interactions as a critical factor in fostering autonomy among disengaged learners. These findings challenge deficit-based perspective on learner motivation and advance autonomy theory by emphasizing its socio-relational dimension. The study suggests EFL educators may integrate clear instructional guidelines with affective and relational pedagogies to address diverse learner dispositions. Practically, the findings underscore the need for teacher training programs to integrate relational strategies with structural management to promote learner autonomy effectively.